Impact of harvest stage on seed yield quality and storability of french bean - Shaheb, Md Rayhan; Islam, Md Nazmul; Nessa, Ashratun; Hossain, Md Altab; Sarker, Ayesha (Bangladesh Journal of Agricultural Research, 2016)
Good quality seeds are one of the least expensive but vital factors influencing yield potential and key to agriculture progress. Studies were conducted both in the field and laboratory with the objective to observe the impact of harvest stage on the seed, quality and storability of French bean. Five harvest stages viz. H1- deep green with light yellow colours of pod, H2-50% green and 50% yellowing of pods, H3-light brown with few yellow colour pods, H4-90% brown colour of pods and H5-100% brown colour and dried pods were considered as treatments for field trial. Harvested seeds were then stored in both cool room and ambient conditions up to 16 months and performed seed quality studies in every 4 months. The treatments combination of laboratory studies were T1: H1 seed storage in cool room (SSCR), T2: H1 seed storage in ambient (SSAB), T3: H2 SSCR, T4: H2 SSAB; T5: H3 SSCR; T6: H3 SSAB; T7: H4 SSCR; T8: H4 SSAB; T9: H5 SSCR and T10: H5 SSAB. Experiments were laid out in a RCBD and CRD in the field and laboratory, respectively. Results revealed that the highest seed yield and quality of French bean was observed in H3. On the contrary, seed harvested in H4 and stored in cool room (with the mean temperature 18-20oC and relative humidity around 60-70%) recorded the highest storability compared to ambient condition. However, seeds harvested in H3 and H5 were also showed better storability in cool room as well as ambient conditions. To sum up, all the seed quality parameters were satisfactorily well up to 12 months of storage then it declined in quality. Bangladesh J. Agril. Res. 40(4): 641-656, December 2015